Study on dietary pattern, cognitive performance and mood among adolescent students in Kota Bharu - Fen, Chen Siau (Universiti Sains Malaysia, 2016)
The objective of this study is to determine the relationship between dietary pattern, cognitive performance and mood among 191 adolescent students aged 14 years in Kota Bharu, Kelantan. Questionnaire consisted of socio-demographic data, breakfast consumption habit, mood assessment, and food frequency questionnaire (FFQ) was distributed. Student's body weight and height were assessed by using SECA weighing scale and body meter, and body mass index (BMI) was calculated. Students' academic achievements were obtained from academic records based on their final examination results. A cognitive test was conducted by using the Raven• s Standard Progressive Matrices (R-SPM) to assess students' cognitive performance. The respondents are made up of 93 male (48.7%) and 98 female students (51.3%). Most of the students (60.2%) reported to have breakfast more than 5 times per week, while 39.8% of the students reported that they had breakfast less than 5 times for the past one week. For dietary intake, the top three food items with highest consumption frequency are rice (99.4%), chicken (54.3%), and bread (50.9%) and these foods were reported to be consumed more than 5 times in a week. There are no significant differences in all academic subject and cognitive test scores among students with different breakfast consumption frequency. Study showed a significant difference in cognitive test score among those with different green leafy vegetables intake frequency (p<0.029). There are significant differences of energy (p<0.05) and tiredness scores (p<0.05) between breakfast eaters and breakfast skippers. In conclusion, breakfast consumption is found to have positive effect on mood state but not on academic and cognitive performances of adolescent students. Further studies with larger population